Criteria of an Effective Training Programme: A Case Study - Lim, Bee Suan (2004)
Well-established criteria of training programme development are crucial to ensure the effectiveness, and most importantly, to reveal the real value of training programme. This study was conducted among the lecturers in Universiti Putra Malaysia to examine the criteria of an effective training programme by identifying the programme development elements, and the approach to programme planning preferred by the professionals. Also, it attempted to compare the perceptions according to the teaching experience, experience in planning training programme, and the frequency of their involvement in training in the last 12 months. By using stratified sampling, 364 lecturers were surveyed, utilizing a structured questionnaire with a response rate of 89.6 percent. The data were analyzed quantitatively by using SPSS programme and was presented in table format. The results of the statistical analyses indicated the components of designing, implementation, and evaluation were perceived to be significantly associated to training effectiveness. By comparison, implementation component was the most important component. The findings further revealed that the sub-components of target audience identification, obtaining credible facilitators/instructors, and formulation of recommendations for changes and future actions were very significant in a successful training. The professionals showed more favour to Classical Viewpoint on planning practice. It was also indicated by the findings, instead of teaching experience and frequency of involvement in training, the professionals' perception on the importance of those criteria varied by their experience in planning training programme. The study therefore recommends that programme developers should take into consideration the training stakeholders' point of views when developing training programme. Further research could be pursued in examining the impact of the input evaluation and/or formative evaluation as to provide insights for improvement of programme development practice.